The management of febrile seizures by pediatricians in Indonesia: adherence to 2016 Indonesian Pediatric Society recommendations and influencing factors - Amanda Soebadi; Rivaldo Suhito; Setyo Handryastuti (Paediatrica Indonesiana, 2023)
Background Although febrile seizures are generally benign, judicious management is needed to prevent inadequate or excessive management. In 2016, the Indonesian Pediatric Society (IPS) issued Recommendations for the Management of Febrile Seizures, but it is unclear whether pediatricians follow these recommendations in their clinical practice. Objectives To evaluate adherence to the 2016 IPS Recommendations for the Management of Febrile Seizures amongst pediatricians in Indonesia, as well as factors influencing adherence. Methods An anonymous online questionnaire was distributed by e-mail to IPS member pediatricians. We collected data on age, year of completion of pediatric residency or subspecialty training, practice region, type of practice, number of febrile seizure patients managed per month, and history of attending teaching sessions on the recommendations. We scored participants’ adherence to the recommendations in terms of pharmacologic treatment, ancillary testing, and prognosis. We also analyzed the difference in scores according to participant characteristics. Results Of 308 participants, 247 (80%) obtained a total adherence score of 50% or more of the highest possible score. Median total adherence score was 63.2% (range 20.6% to 100%) of the highest possible score. Median adherence scores were significantly higher in pediatricians who were 31 to 60-years-old vs. >60-years-old (64.7% vs. 52.9%, P=0.004), completed their residency training within the past <10 years vs. >10 years (64.7% vs. 61.8%, P=0.034), practiced in hospitals vs. clinics or private practices (61.8% vs. 50.0%, P=0.006), were aware vs. unaware of the recommendations (64.7% vs. 52.9%, P=0.02), and had vs. had not read the recommendations (62.7% vs. 50.0%, P=0.01). Most participants (93.5%) reported the recommendations to be feasible in their settings. Obstacles to implementation included lack of medication availability (8/20), lack of time to read the recommendations (8/20), lack of awareness of the recommendations (2/20), and limited infrastructure (2/20). Conclusions Most pediatricians in Indonesia have moderately good adherence to the 2016 IPS Recommendations for the Management of Febrile Seizures. Awareness of the recommendations needs to be raised further and limitations in medication distribution and infrastructure need to be overcome for better adherence.